Mangiferin Enhanced Autophagy via Inhibiting mTORC1 Pathway to Prevent High Glucose-Induced Cardiomyocyte Injury - Hou, Jun; Zheng, Dezhi; Xiao, Wenjing; Li, Dandan; Ma, Jie; Hu, Yonghe (Frontiers in Pharmacology, 2018)
Mangiferin functions as a perfect anti-oxidative compound in the diabetic heart, however the exact mechanism remains to be elucidated. Here, we show the cardioprotective effect of mangiferin under high glucose-induced cardiotoxic condition mainly contributed to enhanced autophagy via suppressing mTORC1 downstream signal transduction. Primary neonatal rat cardiomyocytes were cultured to detect myocytes injury, autophagy and related signal transduction under different doses of glucose and mangiferin treatment. High glucose (30mM) reduced autophagic flux, and increased myocyte apoptosis and death compared with normal glucose (5.5mM) as determined by variation of autophagy markers LC3-II, p62, parkin, GFP-LC3 or mRFP-LC3 fluorescence puncta, cell viability, cleaved caspase3, cleaved PARP apoptosis indices, ROS, MAO and PI death indices. Conversely, mangiferin inhibited hyperglycemia associated oxidative stress by reducing ROS, MAO, cleaved caspase3 and cleaved PARP generation, reestablishing cell viability, mitochondrial membrane potential, and enhancing autophagic flux, thereby preventing myocytes from high glucose-induced toxicity. Furthermore, cardioprotection with mangiferin was potentially related to the decreased mTOR phosphorylation and suppression of mTORC1 downstream signaling pathway. These data indicated the valuable effects of mangiferin on regulation of cardiac autophagy and pointed to the promising utilization for hyperglycemia control.